2007
DOI: 10.1007/s00436-007-0766-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparative studies on the immunogenicity of theronts, tomonts and trophonts of Cryptocaryon irritans in grouper

Abstract: Cryptocaryon irritans is a ciliated obligate parasite of marine fish, causing white spot disease in tropical and sub-tropical regions. Recent studies have shown that fish can mount immune responses against C. irritans and acquire protection. The present study compared the protective immunity in grouper (Epinephelus coioides) against C. irritans induced by theronts, trophonts and tomonts via intraperitoneal (i.p.) injection and tentatively identified an immobilization antigen. Specific antibody titres of immuni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
2
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 33 publications
1
31
2
2
Order By: Relevance
“…Most studies on the protection mechanism against C. irritans have been focused on the antibody responses [20,31]. However, the potential involvement of innate immune responses during the early stages of infection following the invasion of the theronts should also be considered because innate immunity is the first line of defense against many pathogens [32].…”
Section: Experimental Group (Day 13)mentioning
confidence: 99%
“…Most studies on the protection mechanism against C. irritans have been focused on the antibody responses [20,31]. However, the potential involvement of innate immune responses during the early stages of infection following the invasion of the theronts should also be considered because innate immunity is the first line of defense against many pathogens [32].…”
Section: Experimental Group (Day 13)mentioning
confidence: 99%
“…C. irritans, just like Ichthyophthirius multifiliis, is one of the best models to study the antiparasitic immune response in fish. Recently, our lab has reported that fish can mount a humoral immune response to C. irritans and has also shown that a specific antibody could immobilize C. irritans theronts in vitro [33,34]. However, the role of an innate immunity response to C. irritans in fish is more poorly understood.…”
Section: Introductionmentioning
confidence: 97%
“…Previous studies used tomonts (Yambot and Song 2006) or theronts (Luo et al 2007;Bai et al 2008) for challenge exposures. However, in the case of using tomonts, since each tomont has variable excystment time, occurring between 3 and 72 days (Colorni and Burgess 1997), experimental fish must be maintained under continual exposure to C. irritans until all tomonts excyst.…”
Section: Discussionmentioning
confidence: 99%